THE EFFECT OF MOTIVATION AND COMPETENCE ON THE PERFORMANCE OF LECTURERS AT MUHAMMADIYAH SORONG UNIVERSITY - Muhammad Ali; Rais Dera Pua Rawi; Retno Dewi Wijiastuti; Dina Zahra Rimar (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze (1) the effect of work motivation on lecturers performance of Muhammadiyah University of Sorong. (2) the influence of competence on the performance of lecturers Muhammadiyah University of Sorong. (3) The effect of work motivation and competence on the lectures performance at Muhammadiyah University of Sorong. This research uses descriptive and correlation methods with quantitative approach. The population of this study were 135 lecturers with sample of 101 lecturers. Results this study (1) work motivation has positive and significant effect on performance of lecturers Muhammadiyah University of Sorong. (2) Competence has positive and significant effect on the performance of lecturers Muhammadiyah University of Sorong. (3) work motivation and competence have positive and significant an effect simultaneously on the performance of lecturers University of Muhammadiyah Sorong.